Tonga : Operational Procurement Review - World Bank (Washington, DC, 2013)
This procurement assessment in Tonga: (a) reviews existing policies, procedures and practices followed for procurement, with focus on Bank-financed projects and their impact on procurement performance of the Bank portfolio, and recommends measures to improve the procurement performance; and (b) identifies technical assistance (TA) required to introduce international procurement best practices in the country. Tonga does not have any legislation or regulations governing public procurement, and also does not have any formal procurement policies and procedures. Procurement has been decentralized to various Government ministries and departments, with the various institutions following different informal procedures and practices. The risks are high due to lack of capacity, capability and skills in procurement operations, and the volume of procurement would not justify creating procurement skills in each ministry and department. The recommended action plan concludes that procurement support and legal frameworks are high priority items, while procurement manuals, standard documents, capacity building, and training are medium priority.